PENERAPAN TEKNOLOGI PLASMA DENGAN MEMANFAATKAN RANCANG BANGUN OZONE GENERATOR UNTUK PENGAWETAN CABAI MERAH (CAPSICUM ANNUUM L.) GUNA MENDUKUNG KETAHANAN PANGAN NASIONAL - Yudi Pratama; Anna Adianti; Dhyan Prastiwi; Rofiqotul Khasanah; Zaenul Muhlisin; Muhammad Nur (Jurusan Fisika, Fakultas Sains dan Matematika, Universitas Diponegoro, 2016)
In the research, done ozonation of red chili (Capsium annum L.) to getting preservation methods for saving red chili (Capsicium annum L.). To observe the effect treatment of ozone gas, cleaned chili then soaking on water while ozone was dissolving on the water. Then chili that dissolving on water ozonation to be saving on open space, glass cupboard and cooling spacie.On saving to one month have getting that red chili has ozonation and saving on cooling space still in fresh condition.Keywords: Red pepper, ozone, ozone generator